2017
DOI: 10.1016/j.foodhyd.2017.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different hydrocolloids on texture, rheology, tribology and sensory perception of texture and mouthfeel of low-fat pot-set yoghurt

Abstract: Please cite this article as: Phuong T.M. Nguyen, Olena Kravchuk, Bhesh Bhandari, Sangeeta Prakash, Effect of different hydrocolloids on texture, rheology, tribology and sensory perception of texture and mouthfeel of low-fat pot-set yoghurt, (2017),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
155
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(191 citation statements)
references
References 43 publications
17
155
0
3
Order By: Relevance
“…However, depending on the type of polysaccharide, the ability of syneresis is different. In the case by Nguyen et al (), the syneresis of gelatin is reduced to almost 0%, while that of xanthan gum and carrageenan is increased to nearly 2 times at very low concentration (0.01% for xanthan and 0.1% for carrageenan). Electrostatic interactions between polysaccharide and protein seemed to be the main force containing the formation and stability of the mixed gels, and these interactions are probably able to exhibit negatively charged carboxyl groups in the BSM molecules and positively charged side chains of the amino acids in the protein (Chen, Xu, & Wang, ).…”
Section: Resultsmentioning
confidence: 90%
“…However, depending on the type of polysaccharide, the ability of syneresis is different. In the case by Nguyen et al (), the syneresis of gelatin is reduced to almost 0%, while that of xanthan gum and carrageenan is increased to nearly 2 times at very low concentration (0.01% for xanthan and 0.1% for carrageenan). Electrostatic interactions between polysaccharide and protein seemed to be the main force containing the formation and stability of the mixed gels, and these interactions are probably able to exhibit negatively charged carboxyl groups in the BSM molecules and positively charged side chains of the amino acids in the protein (Chen, Xu, & Wang, ).…”
Section: Resultsmentioning
confidence: 90%
“…Less firm yoghurts were also obtained by Wang et al (2015) as the pH values of the samples decreased. Moreover, Nguyen et al (2017) reported that the addition rate of starch has importance in firmness of yoghurt, and a relatively high level of starch is required to remarkably increase the firmness characteristic of yoghurt.…”
Section: Textural Propertiesmentioning
confidence: 99%
“…bulgaricus, and Streptococcus thermophilus to the milk. Due to containing nutritional value and health benefits, yogurt is placed in the category of high‐consumed foods (Nguyen, Kravchuk, Bhandari, & Prakash, ; Sandoval‐Castilla, Lobato‐Calleros, Aguirre‐Mandujano, & Vernon‐Carter, ). During fermentation process, typical milk pH decreases until iso‐electric point of milk via activation of lactic acid bacteria and causes to aggregation of caseins and formation of three‐dimensional gel network (Everett & McLeod, ).…”
Section: Introductionmentioning
confidence: 99%
“…Milk fat has a considerable effect on the development of some quality characteristics such as texture, color, and flavor in dairy products (Zhao, Feng, Ren, & Mao, ). Yogurts manufactured with nonfat milk may exhibit poor texture, low viscosity, and high syneresis depending on absence of fat and reduction of total solid (Nguyen et al, ). However, because of nutritional value and health promoting properties, production and consumption of low‐fat or nonfat dairy products using replacers have been risen over the last two decades in order to respond the consumer demand (Lee & Lucey, ; Romeih, Abdel‐hamid, & Awad, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation